Non-Pharmacological Interventions Using Deep Breathing Relaxation Techniques on Blood Pressure Reduction in Hypertension Sufferers - Amir, Mayasyanti Dewi; Sansuwito, Tukimin Bin; Herlina, Nina; Lawej, Abdualaziz Ibrahim (Qualitative and Quantitative Research Center, 2024)
Hypertension management generally involves the use of pharmacological drugs. However, pharmacological effects are unavoidable and have the potential to disrupt the quality of life. Therefore, efforts to find alternative non-pharmacological therapies are very important. One of the non-pharmacological techniques that has potential is the deep breathing relaxation technique. This study aimed to evaluate the effectiveness of deep breathing techniques in an effort to reduce blood pressure in hypertension sufferers. This research uesd a quasi-experimental research design. The sample in this study was 68 participants divided into 34 participants in the experimental group and 34 participants in the control group. The results showed a significant effect between the pretest variable and the posttest systolic value in the intervention group and between the pretest variable and the posttest diastolic value in the intervention group. Although deep breathing relaxation techniques cannot replace pharmacological treatment completely, they can be beneficial additional therapy in managing hypertension holistically. Proper education about deep breathing relaxation techniques needs to be given to hypertension sufferers in order to get maximum benefits. In addition, this article contributes to public education efforts to increase awareness of deep breathing relaxation techniques as a preventive measure against hypertension. Future research is recommended to combine deep breathing relaxation techniques with other techniques or to use them alongside pharmacological treatment.